Expansion of Acer platanoides L. in areas freed from human impact - Adamczak, Artur (Biodiversity: Research and Conservation, 2006)
The participation of Acer platanoides was studied in so-called synanthropic wildwoods, which developed spontaneously on synanthropic sites after the cessation of direct human impact, in 2002-2004 in Poznań and its surroundings. The ruderal sites where the maple wildwoods arose and floristic differences between them are described on the basis of phytosociological relevés. A. platanoides was the most frequently noted tree species in wildwoods on potential sites of oakhornbeam forests. In many patches it was the dominant plant. With a high constancy it occurred in wildwoods composed of various trees of meso- and eutrophic deciduous forests. The degree of cover by the herb layer and its species richness were low in the young maple wildwoods. Nitrophilous tall-herbs characteristic of forest edges, fallow species of the order Agropyretalia, as well as meadow species had the highest degrees of cover there. The unstable species composition and the domination of common species with wide ecological scales characterized the wildwoods with A. platanoides. The floristic differences between phytocoenoses were connected with the type of occupied anthropogenic site.